A task–technology fit view of job search website impact on performance effects: An empirical analysis from Taiwan - Kuo-Yu Huang; Yea-Ru Chuang (Cogent Business & Management, 2016)
Job search websites (JSWs) are widely used in online job recruitment. However, much of the research on JSWs has focused on technology. To capitalize on the performance associated with JSWs, research addressing the role of JSWs in e-recruiting is required. A nationally representative sample of jobseekers (N = 1,282) was surveyed regarding the JSWs use behaviors of the jobseekers. Task–technology fit is one factor that has been shown to influence both the use of information technology and its performance impacts on effectiveness. This study used the technology-to-performance chain as a framework to address the question of how task–technology fit influences the performance impact of JSWs. The results provided strong evidence of the importance of task–technology fit, which directly influenced performance impacts in e-recruiting, in addition to exerting an indirect influence through the level of utilization. As expected, task–technology fit had a strong influence on jobseeker unemployment duration. In contrast to expectations, social norms did not play a role in the performance impacts of JSWs. However, facilitating conditions and habit had a significant effect on the perceived impact of e-recruiting in JSW utilization.
Keywords: 650